Pasture and subsequent feedlot performance by beef cattle grazing acremonium coenophialum-infected tall fescue and offered different levels of ground grain sorghum - A.S. Freeman; K.P. Coffey (Kansas Agricultural Experiment Station Research Reports, 1993)
One hundred twenty-six crossbred steers and sixty-three crossbred heifers (704 lb BW) were used to evaluate the effects of energy supplementation on animal performance during grazing of endophyte-infected tall fescue and on subsequent feedlot performance. Grazing ADG increased linearly (P.10) by SG that had been fed on pasture.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Sorghum grain; Steers; Heifers; Grazing performance; Feedlot performance; Carcass merit; Fescue; Endophyte